Covalent grafting of molecular photosensitizer and catalyst on MOF-808: effect of pore confinement toward visible light-driven CO2 reduction in water. Issue 4 (22nd March 2021) - Karmakar, Sanchita; Barman, Soumitra; Rahimi, Faruk Ahamed; Maji, Tapas Kumar
Abstract : We have fabricated Zr-MBA-Ru/Re-MOF via post-synthetic modification of MOF-808. The integrated catalyst assembly was used to mimic natural photosynthesis for sunlight-driven CO2 reduction to produce CO in aqueous medium without external sacrificial electron donor. Abstract : The photocatalytic reduction of CO2 in water using a single integrated system utilizing sunlight is the ultimate goal for artificial photosynthesis. Here, we report the design and multistep synthesis of Zr-MBA-Ru/Re-MOF for photocatalytic CO2 reduction via post-synthetic linker exchange (PSE) followed by metalation on MOF-808. The simultaneous covalent immobilization of the molecular [Ru(bpy)3 ] 2+ photosensitizer and [Re(bpy)CO3 Cl] catalyst in the confined space of the MOF resulted in highly efficient CO2 -to-CO formation with a maximum production rate of 440 μmol g −1 h −1 in aqueous medium without any sacrificial electron donor (with selectivity >99%, QE = 0.11). In parallel, under sunlight, this assembly also produces 210 μmol g −1 of CO in 6 h in aqueous medium. In addition, a maximum production rate of 180 μmol g −1 h −1 is observed in MeCN/H2 O (2 : 1) mixed solvent medium with BNAH and TEOA as the sacrificial electron donor (with CO selectivity 69%, QE = 0.22). The high surface area-based Zr-MOF (MOF-808) is robust and water-tolerant, and its post-synthetically modifiable pore surface allows us to covalently attach the molecular photosensitizer and catalyst in the confined nanospace. Covalent grafting of the [Ru(bpy)3 ] 2+ photosensitizer significantly enhances the lifetime of the photoexcited electrons, and the proximity of the catalytic site shortens the transport distance of charge carriers during the reaction, resulting in an efficient catalytic activity. The reaction intermediates are characterized using in situ diffuse reflectance FT-IR (DRIFT), which is well-supported by DFT calculations, and the catalytic cycle involving the reaction mechanism is established.